Evaluation of the Compatibility of the Bpkh Hajj Financing Scheme with Sharia Finance Principles in Medan City - Asriadi, Ari; Marliyah, Marliyah; Siregar, Saparuddin; Muhammedi, Ssonko (JESI (Jurnal Ekonomi Syariah Indonesia), 2024)
This research aims to evaluate the suitability of the BPKH hajj financing scheme with Sharia financial principles in Medan City. In facing economic complexity and developing values, the Hajj Financial Management Agency (BPKH) needs to continue to innovate. The research used a qualitative approach with a focus on Sharia principles, involving analysis of official BPKH documents, financing policies, and in-depth interviews with Hajj pilgrims. Asil shows a strong commitment to the prohibition of usury, with an investment mechanism by Sharia principles. Evaluations from BPKH, MUI, and the Ministry of Religion show support and efforts to increase transparency. Although the majority of Hajj pilgrims are satisfied, there are concerns regarding transparency and distribution of benefits. BPKH leaders stand out as champions of Sharia principles, while Hajj pilgrims' hopes include increased transparency and fair distribution of benefits. In conclusion, the scheme has made positive progress but needs further focus on transparency and distribution of benefits.